Additive Manufacturing: A Novel Method for Developing an Acoustic Panel Made of Natural Fiber-Reinforced Composites with Enhanced Mechanical and Acoustical Properties - Vignesh Sekar; Mohammad Hosseini Fouladi; Satesh Narayana Namasivayam; Sivakumar Sivanesan (Journal of Engineering)
Natural fibers and their composites are being widely used in almost all the applications in this modern era. However, the properties of natural fibers have to be enhanced in order to compete with synthetic fibers. This review paper opens up additive manufacturing, as a novel method for developing an acoustic panel using natural fiber composites with enhanced mechanical and acoustical properties. This approach will help to replace synthetic-based acoustic absorbers with biodegradable composite panels in acoustic applications. This review also covers, poly(lactic acid) as a polymer matrix and its advantages, the available variety of natural fibers as reinforcement in terms of mechanical and acoustical properties. The natural fiber-based filaments used in additive manufacturing and acoustic panels made from the available natural fibers are also elaborated here. This review shows the importance of additive manufacturing and its application to develop novel acoustic panels made of agricultural waste.